Job Performance of Medical Graduates With Compulsory Services in Underserved Rural Areas in China: A Cohort Study - Mingyue Li; Ziyue Wang; Baisong Zhang; Tiantian Wei; Dan Hu; Xiaoyun Liu (Kerman University of Medical Sciences, 2022)
Background  China started a national program in 2010 to train qualified general practitioners with compulsory services program (CSP) in rural and remote areas. While the program has shown positive effects on staffing primary healthcare (PHC) in rural areas, very little is known about how well they perform. This study aims to evaluate the job performance of medical graduates from this program and the influence of program design on job performance.Methods  A cohort study was conducted with graduates from CSP and non-CSP (NCSP) from four medical universities in central and western China. Baseline and three waves of follow-up surveys were conducted from 2015-2020. The pass rate of China National Medical Licensing Examinations (NMLE) and self-reported job performance were used as measurements. Multivariable regressions were used to identify factors affecting job performance.Results  2154 medical graduates were included, with 1586 CSP and 568 NCSP graduates. CSP (90.6%) and NCSP (87.5%) graduates showed no difference in passing the NMLE (P = .153). CSP graduates reported similar job performance with NCSP graduates (CSP, 63.7; NCSP, 64.2); in the multivariable regression, CSP graduates scored 0.32 and 1.36 points lower in the total sample and graduates of 2015-2017, respectively, but not significantly. Having formally funded positions improved the job performance of CSP (β coefficient = 4.87, P < .05). After controlling for Qinghai which adopted a different contracting strategy, "working in hometown" showed significant influence on job performance (β coefficient = 1.48, P < .05).Conclusion  CSP graduates have demonstrated as good job performance as NCSP, proving the competency to provide high-quality care for remote and rural areas. The contracted township health centers (THCs) should provide guidance for CSP graduates, especially in the first few years after graduation. The local government should provide formally funded positions on time and prioritize signing contracts with hometowns or places nearby.